Pengembangan Aplikasi Pengarsipan Surat Masuk dan Keluar untuk Meningkatkan Efisiensi Komunikasi Organisasi Khususnya pada Puskesmas Kimi - Arief Rahman Hakim; Evradus Badii (Jurnal Teknologi dan Informatika, 2024)
In the digital era, efficient office administration management is crucial to supporting organizational productivity and transparency. This article discusses the development of a webbased incoming and outgoing mail application designed to automate the mail management process in government institutions or companies. This application was developed using modern web technologies, including HTML, CSS, JavaScript, and uses a MySQL database for data storage. The research method used is the Waterfall software development model which includes the stages of requirements analysis, system design, implementation, testing and maintenance. The conclusion of this research is that the development of web-based incoming and outgoing mail applications can make a significant contribution to increasing the effectiveness and efficiency of mail administration in organizations.